Doença periodontal, diabete mellitus e hipertensão em gestantes usuárias do Sistema Único de Saúde (SUS) - Moimaz, Suzely Adas Saliba [UNESP]; Lima, Daniela Pereira; Yarid, Sérgio Donha; Saliba, Orlando [UNESP]; Sumida, Dóris Hissako [UNESP]; Okamoto, Ana Claúdia [UNESP] (My University, 2011)
Purpose: To evaluate the association among periodontal disease, diabetes mellitus and arterial hypertension in pregnant women users of the Brazilian Health System (SUS). Methods: The sample consisted of 86 women, with pregnant age between the 4th and 7 th month, submitted to pre-natal attendance in Health Basic Unities (HBUs). Periodontal condition was evaluated by 2 calibrated researchers (Kappa = 0.91) through the Community Periodontal Index (CPI). A sphygmomanometer was used to check the arterial pressure, what was accomplished by the professionals from the HBUs; glycemia test was accomplished through a blood sample collected from the middle finger with a disposable lancet adapted to a lance device (Accu-Chek Softclix Pro; Roche, USA), and for checking the glycemia level, a glycemia monitor was used (Accu-Chek Advantage II, Roche, USA). Data were written on a numbered register form, avoiding patient identification. After, the same data were statistically analyzed through the Fisher Exact Test, in order to evaluate the existence of association between the variables blood glucose and periodontal disease. In this test, a significance level of 0,05 was adopted. Results – Most of the pregnant woman presented periodontal health (58,1%); 41,9% of the research subjects showed at least one sign of periodontal disease, with 31,4% presenting gingivitis and 10,5% periodontitis. Hyperglycemia was detected in 51,2% and it was not found a value of arterial pressure higher than what is considered to be normal. Conclusion: it was not verified a significant association among the presence of periodontal disease, glycemia alteration and arterial hypertension in pregnant women who comprised this research.

Objetivo - avaliar a associação entre doença periodontal, diabete mellitus e hipertensão arterial em gestantes usuárias do Sistema Único de Saúde (SUS). Métodos – a amostra consistiu de 86 mulheres, com idade gestacional entre o 4º e o 7º mês, submetidas ao atendimento pré-natal em Unidades Básicas de Saúde (UBS). A condição periodontal foi avaliada por 2 pesquisadores calibrados ( Kappa = 0,91) pelo do Índice Periodontal Comunitário (IPC). A aferição da pressão arterial foi realizada por profissionais das próprias UBS, utilizando-se esfigmomanômetro e o teste de glicemia foi realizado a partir de amostra de sangue colhida do dedo médio, com lanceta descartável adaptada a um lancetador (Accu-Chek Softclix Pro; Roche, USA), para a aferição utilizou-se um monitor de glicemia (Accu-Chek Advantage II, Roche, USA).Os dados foram anotados em ficha numerada, não permitindo a identificação das pacientes. Posteriormente, os mesmos passaram por análise estatística, sendo aplicado o teste Exato de Fisher para avaliar a existência de associação entre as variáveis glicemia e doença periodontal. No teste foi adotado o nível de significância de 0,05. Resultados – A maioria das gestantes apresentaram saúde periodontal (58,1%), 41,9% dos sujeitos da pesquisa mostraram pelo menos um sinal de doença periodontal, sendo que 31,4% apresentaram gengivite e 10,5% periodontite. A hiperglicemia foi detectada em 51,2 % e não foi encontrado valor de pressão arterial superior ao considerado normal. Conclusão - não se verificou associação significativa entre a presença de doença periodontal, alteração de glicemia e hipertensão arterial nas gestantes participantes da pesquisa.
Periodontal disease, diabetes mellitus and hypertension in pregnant women, users of brazilian health system (SUS)
Keywords: Pregnant women; Diabetes mellitus; Periodontitis; Gingivitis; Hypertension; Gestantes; Diabete mellitus; Periodontite; Gengivite; Hipertensão